Parental phubbing and mental well-being: Preliminary study in Indonesia - Winda Sri Harianti; Irwan Nuryana Kurniawan (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2022)
Parental phubbing is the latest phenomenon that raises concerns because of the changes in habits due to technological developments. It is a form of parental behavior that ignores children as they tend to focus more on activities on gadgets or smartphones. Current parental phubbing studies are limited; however, previous studies have showed the negative impact of parental phubbing on children in late childhood, adolescent, and emerging adulthood, especially on their mental well-being. Therefore, our study aims to determine the impact of parental phubbing on participants’ well-being using a quantitative approach of a comparative independent sample between participants experiencing high and low parental phubbing. The results showed that there were some differences in the effects of parental phubbing on mental well-being, especially mother's parental phubbing (PP-M), for both male and female. In general, parental phubbing affects 3 aspects of mental well-being: a sense of confidence, hope for the future, problem solving and decision-making abilities with a medium effect size. The results indicated that increasingly sophisticated technological developments have affected some changes in behavior and habits through parenting practices, which are not so realized to have negative consequences on the participants’ mental well-being. Our study can also be a reference for new knowledge for practitioners and parents to build an awareness to minimize the further negative impact of parental phubbing behavior on children's development and well-being (in the wide range of developmental stages).